ANALISIS KONDISI JALAN DI KOTA MATARAM (STUDI KASUS RUAS Jl. PENDIDIKAN MATARAM) - BAGUS WIDHI DHARMA S.; MUHAMAD YAMIN (Universitas Mahasaraswati K. Mataram, 2022)
The existence of Jalan Pendidikan connects Mataram District with Ampenan District. The comfort and safety of road users really need to be considered in accordance with the initial planning for the construction of the city road. The increasing number of vehicles that pass every day and the influence of the weather have caused some parts of Jalan Pendidikan to be damaged. This research was conducted to find out the damage that occurred and the activities that needed to be done to improve the condition of the damage.The research method used to determine road damage and the steps taken in road maintenance are the Bina Marga and LHR methods. The survey data for the length of Jalan Pendidikan is 1,570 km. The road is divided into 5 sections with each section being 314 meters long. This division is carried out to determine the condition of the damage more thoroughly. The data is analyzed to determine the value of road damage based on the bina marga. Traffic data collection is carried out to determine traffic density so that the LHR value of the road is obtained. Furthermore, the value of the road class is determined based on the LHR. With the formula UP = 17 – (LHR Class + Road Condition Value) it can be determined the Priority Sequence carried out in the maintenance of Jalan Pendidikan.The results of the research on Jalan Pendidikan, there was light damage on sections 3 to 5 or km to 0.628-1,570 km needed periodic maintenance. Meanwhile, parts 1 and 2 are still in good condition so that the action taken in road maintenance is routine maintenance.